Intervensi Kombinasi Back Massage Dan Acupressure Terhadap Penurunan Nyeri Punggung Pada Ibu Hamil Trimester III - Zhavira Nadya Septari; Riski Oktafia (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2023)
Back pain is one of the most common complaints experienced by pregnant women in the third trimester. One of the treatments to deal with complaints of back pain is a combination of back massage and acupressure. The combination of back massage and acupressure is a therapy used to reduce back pain in pregnant women. The goal of back massage intervention is to reduce muscle tension, and acupressure can increase endorphins to reduce pain by massaging at certain points. The method used is a case study by intervening a combination of back massage and acupressure to reduce back pain in third trimester pregnant women. The measurement instrument uses a numerical scale with an intervention pretest and posttest for 3 days with a duration of 10-15 minutes. The results of the intervention showed that there was a change in the scale of back pain after being given a combination of back massage and acupressure, from a scale of 4 to a scale of 1, so that back massage and acupressure were effective in reducing the scale of back pain in third trimester pregnant women.